Views of Family Caregivers on Advance Care Planning in Advanced Dementia Care in Hong Kong: A Qualitative Thematic Content Analysis Study - Faye Chan; Kuen Lam; Derek Lai; Connie Tong; Christopher Lum; Jean Woo (Health Science Reports, 2025)
ABSTRACT Background Advance care planning (ACP) can be useful for person‐centered dementia care, but it is unfamiliar in Hong Kong. Without advanced discussion of care preferences, it can add stress to family caregivers in decision‐making for future care and impact patients' quality of life. The study aimed to explore family caregivers' views on ACP as well as to understand their perceived outcomes. Methods This qualitative study involved 23 interviews with family caregivers who attended the ACP information talks. The interviews were transcribed and then coded using a thematic content analysis framework. Results Emerging themes include (1) receptive to ACP, (2) mixed emotions, (3) barriers to ACP, (4) family consensus in decision‐making, and (5) benefits of ACP. Family caregivers were open to ACP when initiated by the healthcare team, particularly if patients had previously expressed a desire to forgo treatments, experienced prior crisis episodes, or had multiple hospital admissions. They found starting the conversation challenging, and local culture evaded the topic. Other barriers included the interpretation of filial expectation, building family consensus, and ACP knowledge gap. They needed to overcome internal emotional struggle and related barriers to progress the ACP process. The benefits of ACP included family cohesiveness, enhanced family communication, as well as better preparation for the patient's death, such as minimized unfinished business. For families that could not work through the barriers, the ACP process could become stagnant. Healthcare providers could play a pivotal role in facilitating ACP by addressing the ACP barriers. Conclusions Healthcare professionals can encourage ACP discussion in early dementia care. ACP can raise family caregivers' expectations in end‐of‐life care. The ACP outcome of quality care is more important than documentation of forgoing life‐sustaining treatments or advance (medical) directives. Proper training for healthcare professionals is crucial for initiating and facilitating ACP as well as upholding quality end‐of‐life care.